Effect of Different Salts on Seed Germination of Haloxylon recurvum (Moq.) Bunge ex Boiss., A Halophyte of Indian Arid Zone - Gehlot, Anil Kumar; Sen, David N (Annals of Arid Zone, 2016)
The seeds of Haloxylon recurvmm were subjected to germination in different salts. The results revealed that highest percentage of germination from fresh and old seeds were in NaCl and CaCl2, respectively. The percentage of germination decreased linearly with increase in salt concentration. The vigour index and speed of germination from fresh and old seeds were highest in CaCl2and MgSO4, respectively. The highest germination value and TE4 from fresh and old seeds were in NaCl and MgSO4, respectively. The fresh seeds exhibited higher values of percentage of germination, vigour index, speed of germination, germination value and TE4 as compared to old seeds. The fresh seeds showed rapid and progressive seed germination. The seeds of H. recunum lost their viability with the storage.